2016
DOI: 10.1016/j.jtcme.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical magnitude towards sustainable utilization of wild foliage in Arabian Desert

Abstract: The present investigation was deals with identifying traditional uses of medicinal plants for curing a variety of ailments and degree of religious conservation for retention of ethnobotanical knowledge. The study was carried out in the State of Qatar to document the ethnobotanical uses of 58 medicinally important plant species including identification, botanical name, Arabic name, family, habit, habitat, distribution pattern, and the plant parts used for curing variety of ailments. The documented species belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 11 publications
2
30
0
1
Order By: Relevance
“…Most cited were those categories related to the digestive system (32.8%), followed by respiratory diseases (17%), general symptoms/signs of inflammation (14.5%), nervous system (13.3%) and circulatory system diseases (12.6%). Similar results were already found in other studies [20,24,33,34] indicating that the residents of São Sebastião use medicinal plants as the first line of treatment for most common diseases. …”
Section: Ailments Treated By Medicinal Plantssupporting
confidence: 90%
See 2 more Smart Citations
“…Most cited were those categories related to the digestive system (32.8%), followed by respiratory diseases (17%), general symptoms/signs of inflammation (14.5%), nervous system (13.3%) and circulatory system diseases (12.6%). Similar results were already found in other studies [20,24,33,34] indicating that the residents of São Sebastião use medicinal plants as the first line of treatment for most common diseases. …”
Section: Ailments Treated By Medicinal Plantssupporting
confidence: 90%
“…This survey showed that some 80% of the species with medicinal properties were cultivated in orchards or gardens in backyards of the houses; 15% are considered wild and extracted from the surrounding environments and 5% of the plants were bought at popular markets or drugstores, demonstrating the importance of cultivation as the main source of medicinal plants. Several authors in similar ethnopharmacological studies have also reported that the majority of respondents acquired plants grown in their own backyard cultivars [20,24]. The leaves (78.2%) were the most frequently used plant part for the treatment of diseases, followed by root (8.2%) and seed (6.4%) (Figure 2), which corroborated similar results found in other ethnobotanical studies [29,30].…”
Section: Socio-demographic Informationsupporting
confidence: 87%
See 1 more Smart Citation
“…; Halmy ; Phondani et al. ). In addition, the dynamism of medicinal plant usage is influenced by problems of species disappearance due to over‐collection, overgrazing, habitat loss, impact of urbanization, or impact of global warming, and climate change.…”
Section: Discussionmentioning
confidence: 99%
“…46 Os estudos químicos revelam a presença de cassiaindolina (1), crisofanol (2), fisciona (3), alatonal (4), reina (5), aloe-emodina (6), emodina (7), isocrisofanol (8), alquinona (9), 1,3,8-triidroxi-2-metilantraquinona (10), 47,48 Na Península Arábica e na Grécia, suas folhas são usadas para constipação e cólicas. 49,50 Na África, as folhas de S. alexandrina, aplicadas na pele ou administradas oralmente, são utilizadas contra doenças de pele, lesões e constipação. 21 No Brasil, esta espécie é usada no tratamento contra doenças metabólicas.…”
unclassified